Value of Breast Cancer Molecular Subtypes and Ki67 Expression for the Prediction of Efficacy and Prognosis of Neoadjuvant Chemotherapy in a Chinese Population. Issue 18 (May 2016) - Wang, Jiayu; Sang, Die; Xu, Binghe; Yuan, Peng; Ma, Fei; Luo, Yang; Li, Qing; Zhang, Pin; Cai, Ruigang; Fan, Ying; Chen, Shanshan; Li, Qiao
Abstract : Abstract: The aim of the study was to determine the predictive role of breast cancer subtypes in the efficacy and prognosis of neoadjuvant chemotherapy (NCT) regimens combining taxanes and anthracyclines. Data from 240 patients with breast cancer who received surgery after 4 to 6 weeks of NCT were retrospectively analyzed. The patients were classified into luminal A, luminal B, HER2 overexpression, and triple negative breast cancer (TNBC) as well as low Ki67 (≤ 14%) and high Ki67 (> 14%) expression groups using immunohistochemistry. NCT outcome parameters were pathological complete response (pCR), clinical complete response (CR), partial response (PR), stable disease (SD), and progressive disease (PD) 4 weeks after surgery. Long-term outcome parameters were disease-free survival (DFS) with a follow-up time of 3 to 56 months. pCR rates were 1.6%, 13.4%, 22.6%, and 23.8% in patients with luminal A, luminal B, HER2, and TNBC cancers, respectively. High pCR rates correlated with high Ki67 expression (> 40%) ( P < 0.001, HR = 0.17, 95% CI: 0.074–0.37) and negative estrogen receptor (ER) status ( P < 0.001, HR = 3.74, 95% CI: 1.71–8.12) in a multivariate analysis. However, the DFS rate of luminal A breast cancer was the highest compared to all other groups, but only significantly higher compared to luminal B ( P = 0.035, HR = 1.480, 95% CI: 1.060–1.967) patients and correlated with Ki67 expression > 40% ( P = 0.005). Luminal A type patients derived the least benefit from neoadjuvant chemotherapy but had better long-term prognoses. ER status and Ki67 expression served as efficacy predictors for NCT, whereas only Ki67 expression > 40% correlated with long-term treatment outcomes.